Changes in Immune Activation During Pregnancy and the Postpartum Period in Treated HIV Infection - Schnittman, Samuel R.; Byakwaga, Helen; Boum, Yap; Kabakyenga, Jerome; Matthews, Lynn T.; Burdo, Tricia H.; Huang, Yong; Tracy, Russell P.; Haberer, Jessica E.; Kembabazi, Annet; Kaida, Angela; Moisi, Daniela; et al. (Oxford University Press, 2021)
Pregnant women with HIV (PWWH) have high postpartum morbidity and mortality from infections like tuberculosis. Immunologic changes during pregnancy and postpartum periods may contribute to these risks, particularly the immunoregulatory kynurenine pathway of tryptophan catabolism, which contributes to both HIV and tuberculosis pathogenesis and increases in the early postpartum period. Women with HIV initiating antiretroviral therapy (ART) in the Uganda AIDS Rural Treatment Outcomes (UARTO) cohort who were pregnant at enrollment or became pregnant during observation were studied (n = 54). Plasma kynurenine/tryptophan (KT) ratio, soluble CD14 (sCD14), sCD163, sCD27, interferon-inducible protein 10 (IP-10), D-dimer, interleukin-6, and intestinal fatty-acid binding protein levels were assessed through the first year of ART and at 3-month intervals throughout pregnancy and 1 year postpartum. Biomarker changes were assessed with linear mixed models adjusted for ART duration. Hemoglobin concentration changes were used to estimate pregnancy-related changes in plasma volume. Results. The median pre-ART CD4 count was 134. D-dimer increased through the third trimester before returning to baseline postpartum, while most other biomarkers declined significantly during pregnancy, beyond what would be expected from pregnancy associated plasma volume expansion. IP-10 and sCD14 remained suppressed for at least 12 months postpartum. KT ratio was the only biomarker that increased above prepregnancy baseline postpartum (mean + 30%; P < .001) and remained higher than baseline for ≥9 months (P ≤ .045 for all time points). Several immune activation markers decline during pregnancy and remain suppressed postpartum, but the kynurenine pathway of tryptophan catabolism increases above baseline for ≥9 months postpartum. The mechanisms underlying postpartum kynurenine pathway activity are incompletely understood but may contribute to increased tuberculosis risk in this setting.
Keywords: HIV; Indoleamine 2; 3-dioxygenase-1; Inflammation; Kynurenine/tryptophan ratio; Pregnancy.